2017
DOI: 10.1089/jpm.2016.0280
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Physician Orders for Life-Sustaining Treatment Forms Completed in Nursing Homes

Abstract: We found 30.4% of POLST forms for nursing home residents were not complete or documented clinically contradictory treatment preferences. Improvement in the quality of POLST forms is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 10 publications
0
12
0
3
Order By: Relevance
“…12 In our study, MOST forms were most commonly invalid because of logistical problems with form completion, although 16% still had an inappropriate care preference selection. This is higher than other rates of inconsistent treatment preferences, ranging from 5.6% to 7.3%, and represents a need for consistent interdisciplinary training and quality monitoring to ensure that MOST forms are appropriately implemented in subacute rehabilitation.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…12 In our study, MOST forms were most commonly invalid because of logistical problems with form completion, although 16% still had an inappropriate care preference selection. This is higher than other rates of inconsistent treatment preferences, ranging from 5.6% to 7.3%, and represents a need for consistent interdisciplinary training and quality monitoring to ensure that MOST forms are appropriately implemented in subacute rehabilitation.…”
Section: Discussionmentioning
confidence: 61%
“…This is higher than other rates of inconsistent treatment preferences, ranging from 5.6% to 7.3%, and represents a need for consistent interdisciplinary training and quality monitoring to ensure that MOST forms are appropriately implemented in subacute rehabilitation. 12,13 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, low POLST form completion rates among patients without PPC consultation may be because of providers' lack of familiarity with POLST forms. 18,19 Another notable finding of our study was the relationship between PPC consultation and documentation of mental health disorders. With the documentation of mental health disorders after PPC consultation, it is suggested that PPC consultation may lead to increased identification of mental health disorders, perhaps facilitated when a PPCtrained social worker and/or a psychologist are team members.…”
Section: Discussionmentioning
confidence: 67%
“…However, improvement in the quality of POLST forms is needed. In a study of 938 POLST forms in California nursing homes, 30.4% of POLST forms for residents were not complete or documented clinically contradictory treatment preferences (Rahman et al 2017).…”
Section: Medical Orders At End Of Life (Molst Polst)mentioning
confidence: 99%